Characteristics of Tuberculosis Patients in the Binuang Health Center in the 2021-2022 Period - Muhammad Furqan; Agus Ramadhan (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background: Tuberculosis (TB) is a contagious infectious disease caused by infection with the bacillus Mycobacterium tuberculosis. WHO revealed that TB is the 13th cause of death and the second infectious killer after COVID-19. If TB is not treated or the treatment is incomplete, it can cause dangerous complications and death. The study aims to find out the characteristics of TB patients at the Binuang Community Health Center in the 2021-2022 period. Methods: This research uses descriptive research methods with a cross-sectional study design. Using 70 samples of medical record data from patients who had been diagnosed with TB at the Binuang Community Health Center in 2021-2022. The analysis used was univariate. Results: The majority of patients were in the 51-60-year-old group (21.4%), male (74.3%), had at least elementary school education (37.1%), did not have a job or were self-employed (22.9% ), married (68.6%), bacteriologically confirmed TB group (68.6%), anatomically located in the lungs (85.7%), including new cases (97.1%), category 1 treatment (91, 4%), the result of treatment was cured (64.3%), clinical symptoms of cough > 2 weeks (87.1%), negative HIV status (87.1%), and negative DM status (80%). Conclusion: Based on the results of this research, it is hoped that the community health center will complete data relating to patient illnesses to help research quantity and quality variables. For primary health workers to further increase public knowledge about TB disease and the importance of taking TB medication regularly